2002
DOI: 10.1029/2001jd000896
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of box model calculations and measurements of formaldehyde from the 1997 North Atlantic Regional Experiment

Abstract: [1] Formaldehyde (CH 2 O) measurements from two independent instruments are compared with photochemical box model calculations. The measurements were made on the National Oceanic and Atmospheric Administration P-3 aircraft as part of the 1997 North Atlantic Regional Experiment (NARE 97). The data set considered here consists of air masses sampled between 0 and 8 km over the North Atlantic Ocean which do not show recent influence from emissions or transport. These air masses therefore should be in photochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 38 publications
6
71
0
Order By: Relevance
“…The slope, which has been used frequently to initialise acetone mixing ratios in model calculations, is 6.1 ppt v acetone/ppb v CO (e.g. McKeen et al, 1997;Keim et al, 1999;Frost et al, 2002), and has been observed in the stratosphere during PEM-WEST B. This slope is based on data published by Singh et al (1997), however, the linear relation is described by McKeen et al (1997).…”
Section: Comparison With Literature Valuesmentioning
confidence: 85%
See 1 more Smart Citation
“…The slope, which has been used frequently to initialise acetone mixing ratios in model calculations, is 6.1 ppt v acetone/ppb v CO (e.g. McKeen et al, 1997;Keim et al, 1999;Frost et al, 2002), and has been observed in the stratosphere during PEM-WEST B. This slope is based on data published by Singh et al (1997), however, the linear relation is described by McKeen et al (1997).…”
Section: Comparison With Literature Valuesmentioning
confidence: 85%
“…In global models, emissions of acetone are mostly explicitly described, whereas in box model studies the model is generally constrained to measurements. Since acetone measurements are not always available, the correlation between acetone and CO is often used for model initialisation (McKeen et al, 1997;Keim et al, 1999;Frost et al, 2002). This paper deals with the acetone-CO correlation observed during different aircraft measurement campaigns.…”
Section: European Geosciences Union 2003mentioning
confidence: 99%
“…While direct emissions from fossil fuel combustion, biomass burning, and also automotive exhaust contribute significantly to the burden of atmospheric CH 2 O (Carlier et al, 1986;Garcia et al, 2005), in situ production of CH 2 O by photochemical oxidation of volatile organic compounds appears to be the dominant source on a global scale (Carlier et al, 1986;Warneck, 1999). In remote oceanic areas (Wagner et al, 2002;Weller et al, 2000), in the free troposphere (Frost et al, 2002), and in the stratosphere, only the photochemical oxidation of CH 4 serves as the major source. Apart from the importance of the rather simple CH 2 O molecule in the Earth's atmosphere and far beyond, it is also subject to fundamental research regarding for instance the exact processes during its photolysis (e.g., Moore and Weisshaar, 1983;Townsend et al, 2004;Troe, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several recent formaldehyde measurement/model comparisons in the North Atlantic environment (Weller et al, 2000;Frost et al, 2002; in which all under predict measured formaldehyde concentrations to some degree. Weller et al compared measured average formaldehyde concentrations of 580±160 pptv from a North Atlantic cruise with calculated values based on a box model.…”
mentioning
confidence: 99%